2010
DOI: 10.1039/c0cc04057f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic hydrogen evolution through fully conjugated poly(azomethine) networks

Abstract: Three-dimensional conjugated poly(azomethine) networks were found to be promising candidates for applications in photocatalytic water splitting. Straightforward synthetic protocols lead to fully organic photocatalysts that showed enhanced long-time stability. Furthermore, the catalytic performance of these materials was correlated to the molecular composition and the optoelectronic properties of the samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
165
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(171 citation statements)
references
References 21 publications
(62 reference statements)
4
165
1
Order By: Relevance
“…The most well-known of these photocatalysts are the inorganic solids [1][2][3]6], mostly oxides but also sulfides and selenides, the former including titanium dioxide [13][14][15], the quintessential photocatalyst. Perhaps less well-known, a range of supramolecular systems [16,17] and even organic polymers [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have also been reported to act as photocatalysts. In this mini-review we will discuss computational work on modelling such photocatalysts in terms of the relevant material properties and processes, as well as what we believe to be key aspects to consider when performing such calculations.…”
Section: Which States That Photocatalysis Is the 'Change In The Rate mentioning
confidence: 99%
“…The most well-known of these photocatalysts are the inorganic solids [1][2][3]6], mostly oxides but also sulfides and selenides, the former including titanium dioxide [13][14][15], the quintessential photocatalyst. Perhaps less well-known, a range of supramolecular systems [16,17] and even organic polymers [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have also been reported to act as photocatalysts. In this mini-review we will discuss computational work on modelling such photocatalysts in terms of the relevant material properties and processes, as well as what we believe to be key aspects to consider when performing such calculations.…”
Section: Which States That Photocatalysis Is the 'Change In The Rate mentioning
confidence: 99%
“…Recently, nitrogencontaining poly(azomethine) networks and covalent triazinebased frameworks (CTFs) were shown to have photocatalytic activity with the addition of platinum cocatalysts. [18,19] We have shown that a series of conjugated microporous polymers (CMPs) could facilitate hydrogen evolution from water in the presence of a sacrificial electron donor, without any additional heavy metal cocatalyst. [20,21] Other CMPs have since been studied for photocatalysis [22,23] and recent studies have demonstrated that linear conjugated polymers can have high photocatalytic activities.…”
mentioning
confidence: 99%
“…
The search for new materials has progressed from metal-based photocatalysts to elemental semiconductors (C, Si, P, S, B) [11][12][13][14][15] and recently to metal-free binary materials and polymers, such as carbon nitride [16], boron carbide [17] and conjugated semiconductors [18][19][20]. These researches indicate that photon absorbing materials can be constituted by using lightweight elements such as carbon, nitrogen, and boron, opening up new opportunities for the selection of innovative and intriguing materials for artificial photosynthesis.
…”
mentioning
confidence: 99%